(untitled) (Caderno de Ciências Agrárias, 2018)
The direct calorimetric analysis is the most effective way to obtain caloric value provided by food. Knowing the amount of energy provided by food is essential for the composition of the individuals’ diet. Therefore, this paper aimed to standardize a methodology for quantifying the number of calories present in a fermented milk drink with clove essential oil and in a fermented milk drink. Ten mL of each drink were transferred in to triplicate petri dishes and placed in a forced circulation oven 65 ° C for 24-48 hours to remove moisture to obtain the total solids. These were transferred to a previously tared crucible and inserted into the calorimetric pump until total burning. The results obtained in cal g-1 were converted to Kcal g-1 and finally the amount of Kcal ml-1 of each drink were calculated. The analyzes were submitted to analysis of variance (ANAVA) in a completely randomized design and to the Tukey test was used as means of comparison (p<0.05). The Kcal ml-1 values of the analyzed samples did not differ significantly (p>0.05). It can be concluded that the quantification of calories made by this methodology was effective and could later support studies in which it is necessary to calculate with precision the number of calories provided by fermented dairy drinks. Resumo A análise calorimétrica direta é forma mais eficaz de se obter o valor calórico fornecido pelo alimento. Conhecer a quantidade de energia fornecida pelo alimento é imprescindível para composição da dieta dos indivíduos. Dessa forma, esse trabalho visou padronizar uma metodologia para quantificação de calorias presentes em uma bebida láctea fermentada adicionada com óleo essencial de cravo da índia e uma bebida láctea fermentada. Dez mL de cada bebida foram transferidos para placas de petri em triplicada e colocadas em estufa de circulação forçada 65°C por 24-48 horas, para remoção da umidade a fim de obter os sólidos totais. Esses foram transferidos para um cadinho previamente tarado e inserido na bomba calorimétrica até queima total. Os resultados obtidos em cal g-1 foram convertidos em Kcal g-1 e por fim calculado a quantidade de Kcal ml-1 de cada bebida. As análises foram submetidas à análise de variância (ANOVA) em delineamento inteiramente ao acaso e ao teste Tukey de comparação de médias (p<0,05). Os valores em Kcal ml-1 das amostras analisadas não se diferiram significamente (p>0,05). Pode-se concluir que a quantificação de calorias feita por essa metodologia foi eficaz e poderá auxiliar posteriormente estudos em que necessite calcular com precisão o número de calorias fornecidas por bebidas lácteas fermentadas.